Exponentiated Weibull inverted exponential distribution: Model, properties and applications - Chaudhary, Arun Kumar; Sah Telee, Lal Babu; Yadav, Dhirendra Kumar (NCC Journal, 2021)
This study is based on formulation of a new probability model having four parameters. Parameters of the model are estimated using Maximum likelihood, Least Square and Cramer –von Mises method. Some statistical properties like reliability function, hazard rate functi on, quantile functions are studied. Applicability of the model is tested using a real data set. Box plot and TTT plots are used to explain the nature of the data. For model validation, Q-Q plot, P-P plots as well as information criteria values such as Akaike Information criteria, Bayesian Information criteria, Corrected Akaike information criteria and Hannan- Quinn information criterion values are obtained. For testing the goodness of fit of the model and the model taken for comparison, Kolmogorov- Smirnov, Cramer von-Mises and Anderson darling test are applied. To study of the performance of MLEs, Monte-Carlo simulation is presented. All the calculations are performed using R programming language.